PENGARUH MEKANISME GOOD CORPORATE GOVERNANCE, INDEPENDENSI AUDITOR, KUALITAS AUDIT DAN FAKTOR LAINNYA TERHADAP MANAJEMEN LABA - WELVIN I GUNA; ARLEEN HERAWATY (Jurnal Bisnis dan Akuntansi, 2010)
The aim of this research is to examine the influence of good corporate governance mechanisms, auditor’s independency, leverage, audit quality, profitability and company’s size on the earnings manage-ment practices in manufacturing companies listed in Indonesia Stock Exchange. This research used 40 listed manufacturing companies in Indonesia Stock Exchange, selected using purposive sampling method, during the research period 2006 until 2008. Data were analyzed using multiple regression method. The result of the analysis indicated that leverage, audit quality and profitability had influence on earnings management practice. It means that leverage, audit quality by audit firms size and profit or loss that was reported by the management will motivate the management in doing the earnings management practices.